The effect of a cadence retraining protocol on running biomechanics and efficiency: a pilot study - Hafer, J. F.; Brown, A. M.; deMille, P.; Hillstrom, H. J.; Garber, C. E. (Journal of Sports Sciences, 2015)
Many studies have documented the association between mechanical deviations from normal and the presence or risk of injury. Some runners attempt to change mechanics by increasing running cadence. Previous work documented that increasing running cadence reduces deviations in mechanics tied to injury. The long-term effect of a cadence retraining intervention on running mechanics and energy expenditure is unknown. This study aimed to determine if increasing running cadence by 10% decreases running efficiency and changes kinematics and kinetics to make them less similar to those associated with injury. Additionally, this study aimed to determine if, after 6 weeks of cadence retraining, there would be carryover in kinematic and kinetic changes from an increased cadence state to a runner`s preferred running cadence without decreased running efficiency. We measured oxygen uptake, kinematic and kinetic data on six uninjured participants before and after a 6-week intervention. Increasing cadence did not result in decreased running efficiency but did result in decreases in stride length, hip adduction angle and hip abductor moment. Carryover was observed in runners` post-intervention preferred running form as decreased hip adduction angle and vertical loading rate.